2009
DOI: 10.21236/ada511511
|View full text |Cite
|
Sign up to set email alerts
|

Subtle Cognitive Effects of Moderate Hypoxia

Abstract: The public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing the burden, Increasing worldwide concern over the effects of moderate altitude exposure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 2 publications
1
8
1
Order By: Relevance
“…Previous investigators have reported that cognitive function was impaired after 60 min of hypoxia exposure and complex cognitive tasks were impaired before simple tasks (Cudaback 1984;Adam et al, 2008;Hewett et al, 2009;Kryskow et al, 2013). The data support these previous investigations in that some of our indices of cognitive function were impaired during at the B-Hypo compared to B-Norm.…”
Section: Cognitive and Physiological Measurements At Rest In Hypoxiasupporting
confidence: 85%
“…Previous investigators have reported that cognitive function was impaired after 60 min of hypoxia exposure and complex cognitive tasks were impaired before simple tasks (Cudaback 1984;Adam et al, 2008;Hewett et al, 2009;Kryskow et al, 2013). The data support these previous investigations in that some of our indices of cognitive function were impaired during at the B-Hypo compared to B-Norm.…”
Section: Cognitive and Physiological Measurements At Rest In Hypoxiasupporting
confidence: 85%
“…As already stated, the difference of findings in literature on the effect of hypoxia on high cognitive process has been mainly explained by divergences in the methods used (Davranche et al, 2016). In many situations, however, no significant effects on cognitive performance have, as in the present study, been detected (Hewett, Curry, Rath, & Collins, 2009;Komiyama et al, 2015;Latshang et al, 2013;Legg et al, 2014;Pavlicek et al, 2005;Tripathi, Apte, & Mukundan, 2005). It can, therefore, be safely concluded that people's information integration capacities are not affected by hypoxia, even if acclimatization to it has not taken place, and as far as it is not too severe; that is, corresponding to an altitude that is lower than 4500 m.…”
Section: Figure 2 Patterns Of Results Showing the Perceived Relationscontrasting
confidence: 43%
“…In acute hypoxia, especially when it is probed in laboratory settings devoid of other confounding factors as cold, fatigue and high level of physical exertion, the altitude of up to 3880 (+/− 500) m have not produced reliable cognitive deterioration in numerous studies (for no effect see Crow and Kelman, 1973 ; Paul and Fraser, 1994 ; Gustafsson et al, 1997 ; Takagi and Watanabe, 1999 ; Hewett et al, 2009 ). In longer sojourns, hypoxia attenuates with long-term acclimatization on various physiological levels, for example, red blood cell count increases in the first 5–6 weeks (Zubieta-Calleja et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%